Satyrium nepalense: A RARE MEDICINAL ORCHID OF WESTERN HIMALAYA (INDIA); PHYTOCHEMICAL SCREENING, ANTIMICROBIAL EVALUATION AND CONSERVATION STUDIES - Mishra, Abhay Prakash; Saklani, Sarla (Indonesian Journal of Pharmacy, 2012)
Satyrium  nepalense  is  an  endangered  medicinal  herb  found at  the higher altitude of 2400-5000m. Local inhabitant used tubers of  Satyrium  nepalense  as  an  energetic  tonic  and  as  an  important medicine  to  cure  different  type  of  fever  in  traditional  health  care system  of  Uttarakhand  (INDIA).  Present  study  was  carried  out  to evaluate  the  phytochemical,  antibacterial  screening  against  four (Streptococcus  mutans,  Pseudomonas  aeruginosa,  Staphylococcus aureus  and  Klebsiella  pneumoniae)  microorganisms  in  methanolic extracts  and  habitat  studies  for  conservation  of  S.  nepalense. Tubers  of  Satyrium  nepalense  were  extracted  separately  with methanol  by  hot  extraction  process  using  soxhlet  apparatus.  The extracts  were  subjected  to  Lyophilization  to  get  dry  extract  and preserved  in  aseptic  condition.  The  different  group  reagents  used for  phytochemical  screening  as  dragendorffs’s  for  alkaloid, molisch’s  test  for  carbohydrates,  shinoda  test  for  flavonoids  etc. Antibacterial  study  was  carried  out  by  disc  diffusion  method.  The highest  zone  of  inhibition  was  recorded  as  15.0±0.00  mm  against Klebsiella  pneumonia  and  15.0±0.82  mm  against  Staphylococcus aureus.  Phytochemical  screening  shows  the  presence  of  alkaloids, carbohydrates/glycosides,  flavonoids  and  unsaturated  sterols/triterpenes  in  Satyrium  nepalense.  The  result  indicates  that methanolic  extract  of  Satyrium  nepalense  shows  potent antibacterial activity against all four bacterial strains.Key  words:  Uttarakhand,  Satyrium  nepalense,  medicinal  orchid,  antibacterial, phytochemicals